Kinetic studies of the AOP radical-based oxidative and reductive destruction of pesticides and model compounds in water. (April 2018) - Clark, Kristin K.; Mezyk, Stephen P.; Abbott, Amberashley; Kiddle, James J.
Abstract: Absolute second-order rate constants for hydroxyl radical (HO ) reaction with four organophosphorus pesticides, malathion, parathion, fenthion and ethion, and a suite of model compounds of structure (EtO)2 P(S)-X (where X = Cl, F, SH, SEt, OCH2 CF3, OEt, NH2, and CH3 ) were measured using electron pulse radiolysis and transient absorption techniques. Specific values were determined for these four pesticides as k = (3.89 ± 0.28) x 10 9, (2.20 ± 0.15) x 10 9, (2.02 ± 0.15) x 10 9 and (2.93 ± 0.10) x 10 9  M −1  s −1, respectively, at 20 ± 2 °C. The corresponding Brönsted plot for all these compounds demonstrated that the HO oxidation reaction mechanism for the pesticides was consistent with the model compounds, attributed to initial HO -adduct formation at the P(S) moiety. For malathion, steady-state 60 Co radiolysis and 31 P NMR analyses showed that hydroxyl radical-induced oxidation produces the far more potent isomalathion, but only with an efficiency of 4.9 ± 0.3%. Analogous kinetic measurements for the hydrated electron induced reduction of these pesticides gave specific rate constants of k = (3.38 ± 0.14) x 10 9, (1.38 ± 0.10) x 10 9, (1.19 ± 0.12) x 10 9 and (1.20 ± 0.06) x 10 9  M −1  s −1, respectively, for malathion, parathion, fenthion and ethion. Model compound measurements again supported a single reduction reaction mechanism, proposed to be electron addition at the PS bond to form the radical anion. These results demonstrate, for the first time, that the radical-based treatment of organophosphorus contaminated waters may present a potential toxicological risk if advanced oxidative processes are used. Highlights: Absolute radical reaction rate constants with organophosphorus pesticides in water. Kinetics of pesticides and model compounds identified initial reaction mechanisms. More toxic isomalathion produced by hydroxyl radical oxidation of malathion.